Atlantic and Pacific halibut co‐management initiatives by Canadian fishermen's organizations. Issue 6 (15th August 2018) - Pinkerton, Evelyn; Allain, Marc; Decker, David; Carew, Ken
Abstract: Many fisheries managers and neoliberal fisheries economists promote Individual Transferable Quotas (ITQs) as a solution to the race for fish which can cause rent dissipation under competitive quota or open access fisheries. These actors consider the Canadian Pacific halibut ITQ fishery an example of successful achievement of these objectives. However, critics note the weak performance of this management model in distribution of benefits, increased capital costs to fishermen, deteriorating safety conditions, reductions in crew income and barriers to entry. They point to the layup system which successfully managed effort in the Pacific halibut fishery for four decades prior to the introduction of ITQs. A system similar to the layup has been used for Atlantic halibut since 2013, initiated by the Fish Food and Allied Workers (FFAW) representing owner‐operator license holders in the halibut fishery off the coast of western Newfoundland and southern Labrador. The FFAW rejected the two halibut management plan options presented to them by Fisheries and Oceans Canada: the status quo (a competitive 12‐hr "derby" fishery) or IQs, likely leading to ITQs. Instead, the FFAW worked with license holders to develop a management plan that required harvesters to choose between different fishing periods that spread fishing opportunities over time. This approach improved conservation results, delivered strong economic returns, distributed benefits widely to active fishermen, and allowed an even flow into the market. The authors consider the advantages of these Canadian east and west coast halibut co‐management systems and their broader application.